2019
DOI: 10.1186/s42523-019-0002-6
|View full text |Cite
|
Sign up to set email alerts
|

Distinct microbiotas of anatomical gut regions display idiosyncratic seasonal variation in an avian folivore

Abstract: Background: Current knowledge about seasonal variation in the gut microbiota of vertebrates is limited to a few studies based on mammalian fecal samples. Seasonal changes in the microbiotas of functionally distinct gut regions remain unexplored. We investigated seasonal variation (summer versus winter) and regionalization of the microbiotas of the crop, ventriculus, duodenum, cecum, and colon of the greater sage-grouse (Centrocercus urophasianus), an avian folivore specialized on the toxic foliage of sagebrush… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(28 citation statements)
references
References 67 publications
2
26
0
Order By: Relevance
“…Previous studies on wild birds have demonstrated low bacterial diversity and community composition differences in the midgut region (stomach and small intestine) compared to the crop microbiota. This suggests that the highly-acidic conditions in the midgut region acts as a barrier for environmental and foodborne bacteria [14,66,76,77]. This is further evident when we look at previously published mealworm gut microbiomes [78], where only a small fraction of the microbiome consists of bacterial genera that we identi ed in the gut microbiomes of mealworm-fed P. major.…”
Section: P Major Gut Microbiomes Respond To Diet Changes But Not Asmentioning
confidence: 73%
“…Previous studies on wild birds have demonstrated low bacterial diversity and community composition differences in the midgut region (stomach and small intestine) compared to the crop microbiota. This suggests that the highly-acidic conditions in the midgut region acts as a barrier for environmental and foodborne bacteria [14,66,76,77]. This is further evident when we look at previously published mealworm gut microbiomes [78], where only a small fraction of the microbiome consists of bacterial genera that we identi ed in the gut microbiomes of mealworm-fed P. major.…”
Section: P Major Gut Microbiomes Respond To Diet Changes But Not Asmentioning
confidence: 73%
“…Sharon A. Huws I am proud to announce the official launch of Animal Microbiome. We launch today with 'Distinct microbiotas of anatomical gut regions display idiosyncratic seasonal variation in an avian folivore [1]' and have many articles accepted and ready for publication in due course.…”
Section: Welcome To Animal Microbiomementioning
confidence: 99%
“…Gut bacterial taxa play an important role in organismal health, including regulating digestion [1], nutrient uptake [2], fat metabolism [3], and vitamin synthesis [4]. A range of factors influence gut bacterial community composition and diversity, including diet [5], environment [6,7], and seasons [8]. However, the unique life cycle of birds, especially migratory birds, makes it interesting to study their gut bacterial community [9].…”
Section: Introductionmentioning
confidence: 99%